2005
DOI: 10.1159/000087627
|View full text |Cite
|
Sign up to set email alerts
|

Asystole and Severe Bradycardia in Preterm Infants

Abstract: Transient episodes of apnea and bradycardia are common in preterm infants. Pronounced asystole or sinus arrest, however, is relatively rare and the clinical significance of such events is unknown. Objective: The purpose of our study was to: (1) evaluate the prevalence of severe bradycardic and asystolic events in infants studied with polygraphic cardiorespiratory monitoring, (2) characterize these events, and (3) correlate the events with other clinical findings. Methods: A total of 583 studies were performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Alternative causes to be considered include apnea, seizures, medication effects, and neurocardiogenic mechanisms. 255,256 In carefully selected cases, cardiac pacing has been effective in the prevention of recurrent seizures and syncope in infants with recurrent pallid breath-holding spells associated with profound bradycardia or asystole. 257 A variant of the bradycardia-tachycardia syndrome, sinus bradycardia that alternates with intra-atrial re-entrant tachycardia, is a significant problem after surgery for congenital heart disease.…”
Section: Pacing In Children Adolescents and Patients With Congenitamentioning
confidence: 99%
“…Alternative causes to be considered include apnea, seizures, medication effects, and neurocardiogenic mechanisms. 255,256 In carefully selected cases, cardiac pacing has been effective in the prevention of recurrent seizures and syncope in infants with recurrent pallid breath-holding spells associated with profound bradycardia or asystole. 257 A variant of the bradycardia-tachycardia syndrome, sinus bradycardia that alternates with intra-atrial re-entrant tachycardia, is a significant problem after surgery for congenital heart disease.…”
Section: Pacing In Children Adolescents and Patients With Congenitamentioning
confidence: 99%
“…As early as the 10th minute of HUT, all patients demonstrated a significant drop in blood pressure followed by a period of ventricular pauses i.e. asystole (defined as prolonged cardiac pauses exceed 3 s) [3,12]. Simultaneously, all patients reported increasing dizziness with variable other symptoms of sensory disturbance, blurred vision, and nausea.…”
Section: Methods and Resultsmentioning
confidence: 97%
“…In line with the latter data, Dorostkar et al [7] reported that GER was temporally related to only 1 of 22 events with heart rate <20/min, and Di Fiore et al [8], studying a large sample of preterm infants, also found no evidence for a temporal relationship between acid-based GER and apnea. In fact, Corvaglia’s group was originally one of the few to have identified an apparent temporal relationship between GER and AOP.…”
mentioning
confidence: 80%